Temperature measurements in geotechnical studies using low-noise, high-resolution digital techniques - Woodbury, Allan D.; Narod, B.; Chandra, B.; Bennest, J. R. (Canadian Geotechnical Journal, 1991)
In this paper we show how temperatures can be of use as a normal well-logging tool and as an aid in site hydrogeological analysis. A back-portable, digital temperature-logging system has been developed. The system consists of a digital probe, a small surface unit, a back-portable cable reel, and a lap-top computer. The probe is 2.54 cm outside diameter and has been used in 3.05 cm inside diameter tubing. The overall accuracy of the probe is ±0.01 °C in the range −40 to + 40 °C. Power consumption is less than 30 mA at 12 V direct current. The probe's capability and the thermal methodology are demonstrated at a Manitoba Hydro project site along the Nelson River in northern Manitoba. The thermal regime of the site displays a myriad of effects, from permafrost to transient-advective environments. Surface temperatures are affected by permafrost, particularly through the postglacial deposits. Permafrost is less evident towards the river on the north side, undoubtedly due to warming effects from river and ice staging. Although only one set of temperatures has been obtained at the site, the inclusion of the thermal data aided significantly in identifying effects that otherwise would have been missed in a purely hydrogeologic investigation. Key words: digital thermal measurements, geotechnical studies, permafrost, groundwater.